2020
DOI: 10.4236/ojapps.2020.107034
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Injection Timing and Injection Duration of a Diesel Engine Running on Pure Biodiesel SME (Soya Methyl Ester)

Abstract: This study was carried out to predict the impact of injection timing and injection duration on engine brake power and Nitrogen Oxides emissions in a diesel engine using biofuel Soya Methyl Ester (SME). Predictions were accomplished at three different injection timings 10˚, 5˚ Crank Angle (CA) before Top Dead Center (bTDC) and 0˚ CA at Top Dead Center (TDC) and four injection durations 20˚, 25˚, 30˚, 35˚ CA. The study was conducted using a simulation software (Diesel-RK). The predicted results showed that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Alghafis and Raouf [15] investigated the impact of injection timing and injection duration on engine brake power and NO x using Diesel-RK simulation software. They operated the engine at different engine speeds of 1000, 1500, 2000, 2500, 3000 and 4000 rpm, at different injection timing of 10˚ CA-bTDC, 5˚ CA-bTDC and 0˚ CA-TDC and at different injection duration of 20˚, 25˚, 30˚, 35˚ and 40˚ CA.…”
Section: Introductionmentioning
confidence: 99%
“…Alghafis and Raouf [15] investigated the impact of injection timing and injection duration on engine brake power and NO x using Diesel-RK simulation software. They operated the engine at different engine speeds of 1000, 1500, 2000, 2500, 3000 and 4000 rpm, at different injection timing of 10˚ CA-bTDC, 5˚ CA-bTDC and 0˚ CA-TDC and at different injection duration of 20˚, 25˚, 30˚, 35˚ and 40˚ CA.…”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that ignition delay and emission in biodiesel blends are influenced largely by fuel mixing concentration, injection pressure and ambient temperature which affects the autoignition and combustion. [9] investigated the impact of injection timing and duration on engine brake power and NO x using Diesel-RK simulation software. They operated the engine at different engine speeds of 1000, 1500, 2000, 2500, 3000 and 4000 rpm, at different injection timing of 10° CA-bTDC, 5° CA-bTDC and 0° CA-TDC and different injection duration of 20°, 25°, 30°, 35° and 40° CA.…”
Section: Introductionmentioning
confidence: 99%